Integrating network pharmacology and experimental verification to explore the protective effects of Evodia rutaecarpa in ischemic stroke - Zhixuan Huang; Jian Liu; Hui Li; Hengjun Huang; Yangwen Ai; Dongyue Zhou (PLoS ONE, 2025)
Background Evodia rutaecarpa is a traditional Chinese herbal medicine known for its potential benefits in the treatment of cardiovascular and cerebrovascular diseases. Despite its recognized effects, the effects of Evodia rutaecarpa on ischemic stroke (IS), along with the primary active compounds and precise mechanisms of action, require elucidation. Methods Network pharmacology analyses and molecular docking were performed to integrate information related to Evodia rutaecarpa and IS. Cell oxygen–glucose deprivation (OGD) and rat middle cerebral artery occlusion (MCAO) models were established to simulate cerebral ischemic injury. The effects of rutaecarpine on these models were evaluated to assess its effect on IS. Results Network pharmacological analysis indicated that rutaecarpine from Evodia rutaecarpa showed therapeutic effects against IS. The mechanism underlying these effects mainly involved the mitogen-activated protein kinase (MAPK), and targets such as matrix metalloproteinase (MMP)-9, caspase 3 and MMP-2 may be activated to exert these effects. In vitro studies showed that rutaecarpine significantly improved the mitochondrial membrane potential of HT22 cells, reduced the production of reactive oxygen species, and reversed OGD-induced cytotoxicity. In the MCAO rat model, pretreatment with rutaecarpine significantly reduced neuronal death, decreased infarct volume, and improved neurological functional deficits. In addition, rutaecarpine alleviated damage to the blood–brain barrier in the brain tissue. These effects may be related to the regulation of the MAPK-mediated MMPs pathway. Conclusion This study revealed the neuroprotective effects and molecular mechanisms of rutaecarpine on IS, providing a new theoretical basis for the clinical application of Evodia rutaecarpa.